PENGARUH DISIPLIN DAN PELATIHAN KERJA TERHADAP KINERJA PEGAWAI DINAS SOSIAL PROVINSI BENGKULU - Ahmad Zarovi Kurniawan; Mardhiyah Dwi Ilhami (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to determine the effect of work discipline and job training on employee performance at the Social Service Office of Bengkulu Province. Issues related to discipline and training effectiveness are a major concern as they affect the quality of public services. This research employs an associative quantitative approach with a sample of 109 employees and uses multiple linear regression analysis. Partial test results show that work discipline has a significant effect on employee performance (t = 4.803; sig. = 0.000), while job training does not have a significant effect (t = -0.813; sig. = 0.418). However, simultaneous testing indicates that discipline and training together have a significant effect on employee performance (F = 54.712; sig. = 0.000), with an Adjusted R² value of 0.501, meaning that 50.1% of the variation in performance can be explained by both variables. Keywords: Work Discipline, Job Training, Employee Performance